(untitled) (Journal of Computational Mathematics, 1998)
In this paper, we study fully discrete spectral method and long time behavior of solution of generalized Kuramoto-Sivashinsky equation with periodic initial condition. We prove that the large time error estimation for fully discrete solution of spectral method. We prove the existence of approximate attractors A_N, A_N^k respectively and d (A_N, A)→ 0, d (A_N^k, A) → 0.